How do audit team industry and client‐specific experience impact audit effort and audit fees?. Issue 1 (28th January 2021) - Contessotto, Christine; Knechel, W. Robert; Moroney, Robyn
Abstract : Prior research into the effect of different types of experience on audit fees and audit effort has been primarily conducted at the individual, office or firm level but rarely at the team level. An important motivation for team level research is that within team variation could influence the conduct, quality and pricing of an audit. Audit team industry specialization and client‐specific experience have been associated with higher audit quality. We extend this research by investigating the effect of audit team industry experience and client‐specific experience on audit production hours (effort) and fees. Using proprietary team‐level data provided by two Australian mid‐tier firms, we find that audit team client‐specific experience is associated with higher effort and fees. Although team‐level industry experience is not associated with effort or fees, it is associated with the use of lower ranked auditors. Our results suggest that audit teams with industry experience enjoy cost savings, while audit teams with client‐specific experience incur additional effort, perhaps due to the provision of value‐added services.